2014
DOI: 10.1111/pme.12567
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Pressure Pain Hypersensitivity and Upper Limb Mechanosensitivity in Breast Cancer Survivors: A Case–Control Study

Abstract: Breast cancer survivors present bilateral and widespread neural hypersensitivity, as they did in muscular tissue in previous studies. Breast cancer survivors demonstrate a reduction in ROM during ULNTs in the affected side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…In a sample of BCS suffering from chronic pain ( n = 305), 59% presented allodynia, and referred to pain sensitization following normally non‐painful stimulation (Hamood, Hamood, Merhasin, & Keinan‐Boker, ). Further studies have suggested an increased sensitivity to pain in the upper limb as a sign of CS mechanism in women after standard treatment of BC (Caro‐Morán et al., ), including mastectomy (Fernández‐Lao et al., ). Another study analyzed pressure pain sensitivity threshold through pressure algometry, allowing to obtain topographical pressure sensitivity maps from the shoulder region in BCS.…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of BCS suffering from chronic pain ( n = 305), 59% presented allodynia, and referred to pain sensitization following normally non‐painful stimulation (Hamood, Hamood, Merhasin, & Keinan‐Boker, ). Further studies have suggested an increased sensitivity to pain in the upper limb as a sign of CS mechanism in women after standard treatment of BC (Caro‐Morán et al., ), including mastectomy (Fernández‐Lao et al., ). Another study analyzed pressure pain sensitivity threshold through pressure algometry, allowing to obtain topographical pressure sensitivity maps from the shoulder region in BCS.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral deficits in neural mechanosensitivity in women with unilateral BrCA suggest widespread, generalized hypersensitivity. 42,43 Additionally, alterations in body image are common with BrCA 16 and may be more generalized to both breasts rather than just the affected side. Further research into mechanisms for widespread alterations in body image and LRJT performance after BrCA is warranted.…”
Section: Impairments In Lrjt Performancementioning
confidence: 99%
“…Axillary treatment for breast cancer, which is surgical removal of the lymph nodes in the armpit (axilla) or axillary radiotherapy, can contribute to upper limb dysfunction (ULD). Symptoms of ULD include pain, numbness, decreased shoulder range of motion (ROM), reduced strength, joint restrictions, axillary web syndrome (lymphatic cording), and development of arm volume changes or lymphoedema due to interruption or damage to the axillary lymphatic system [ 1 7 ]. Severity of symptoms and prevalence vary considerably because of differences in diagnostic criteria, assessment methods and time points among studies.…”
Section: Introductionmentioning
confidence: 99%